Analisis Peran Perpustakaan Raja Naga Jambe dalam Meningkatkan Budaya Membaca Masyarakat di Kabupaten Dairi - Zakia Pasi, Rahma; Susanti , Neila (Literatify: Trends in Library Developments, 2024)
This research analyzes the role of Raja Naga Jambe Library in improving the reading culture of the community in Dairi Regency, North Sumatra. Libraries have great potential in encouraging people's interest in reading, but their mere existence does not guarantee the realization of a strong reading culture. This research identifies programs, supporting and inhibiting factors and efforts made by the library in improving reading culture. The method used is a case study by collecting data through observation, interviews, and document studies. The results show that Raja Naga Jambe Library plays a role in providing access to information, supporting education, and empowering the community through literacy programs. The main supporting factors are community involvement, government support and the provision of adequate facilities. Meanwhile, significant inhibiting factors are the lack of budget and low public awareness of the importance of reading. Efforts made to overcome these obstacles include awareness campaigns through social media, promotions, socialization to village/school libraries, and yearbook procurement.